(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
In various stories from the oral tradition, we see water taking on different roles. A notable example is the role of water in Charles Perraults fairy tale The fairies, published in Tales of mother goose or stories of ancient times (1697). This work was given a Spanish edition, Tales of yesteryear (1986), which contains drawings by Gustave Dor. In the drawing of The fairies, you can see the image of a young woman holding a huge pitcher under the tap of a natural spring of water that represents feminine pain and purity. In the 20th century, the Uruguayan writer and poet Juana de Ibarbourou used the theme of water extensively in her work, such as in the prose poetry of The fresh pitcher (1920) and in Triptych, a series of three poems from Dualism (1953). The aim is to carry out a comparative reading of a contrastive and qualitative nature between these three authors based on the idea of a new comparatism (Coutinho, 2016). Subsequently, the aim is to reflect on how this emerging new comparatism can be realised in Spanish language teaching in Brazilian schools through a new humanism (Coutinho, Palermo & Schmidt, 2021) in rural Latin American communities, such as Sopa, a rural community located in the Jequitinhonha Valley in Minas Gerais, Brazil. This new relationship established with comparative literature and its teaching can give new meaning to the relationships that young Brazilian readers have with foreign literature, as well as to the way teachers relate to this little-known literature in Brazil.